Semi‐random graph process. Issue 3 (21st October 2019) - Ben‐Eliezer, Omri; Hefetz, Dan; Kronenberg, Gal; Parczyk, Olaf; Shikhelman, Clara; Stojaković, Miloš
Abstract : We introduce and study a novel semi‐random multigraph process, described as follows. The process starts with an empty graph on n vertices. In every round of the process, one vertex v of the graph is picked uniformly at random and independently of all previous rounds. We then choose an additional vertex (according to a strategy of our choice) and connect it by an edge to v . For various natural monotone increasing graph properties 𝒫, we prove tight upper and lower bounds on the minimum (extended over the set of all possible strategies) number of rounds required by the process to obtain, with high probability, a graph that satisfies 𝒫 . Along the way, we show that the process is general enough to approximate (using suitable strategies) several well‐studied random graph models.